2006
DOI: 10.1098/rspb.2006.3622
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and disease resistance in a social insect: effects of heterozygosity on immunocompetence in the termite Zootermopsis angusticollis

Abstract: Recent research has shown that low genetic variation in individuals can increase susceptibility to infection and group living may exacerbate pathogen transmission. In the eusocial diploid termites, cycles of outbreeding and inbreeding characterizing basal species can reduce genetic variation within nestmates during the life of a colony, but the relationship of genetic heterogeneity to disease resistance is poorly understood. Here we show that, one generation of inbreeding differentially affects the survivorshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 76 publications
(113 reference statements)
9
80
3
Order By: Relevance
“…In contrast to previous studies in insects, which found no evidence that inbreeding would compromise the immune system (e.g. Stevens et al, 1997;Gerloff et al, 2003;Calleri et al, 2006), we found that inbreeding reduced a female's ability to encapsulate nylon monofilament markedly. However, this effect was not found in males after taking into account variation within families (Table 2; though a reduction considerably less than observed in inbred females was observed if family effects were ignored; Figure 1).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast to previous studies in insects, which found no evidence that inbreeding would compromise the immune system (e.g. Stevens et al, 1997;Gerloff et al, 2003;Calleri et al, 2006), we found that inbreeding reduced a female's ability to encapsulate nylon monofilament markedly. However, this effect was not found in males after taking into account variation within families (Table 2; though a reduction considerably less than observed in inbred females was observed if family effects were ignored; Figure 1).…”
Section: Discussioncontrasting
confidence: 55%
“…For example, in the bumble-bee, Bombus terrestris (L.), inbreeding (brothersister mating) did not have any effect on innate immune defence or body size of the offspring (Gerloff et al, 2003). In the termite, Zootermopisis angusticollis, inbreeding neither decreased encapsulation response nor resistance against bacterial or fungal disease (Calleri et al, 2006). Similarly, inbred lines of the flour beetle Tribolium castaneum did not differ from a stock population in their resistance to parasitic nematodes (Stevens et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…However, we are only beginning to understand which mechanisms and pathways may underlie the reduced fitness of inbred individuals (Calleri et al, 2006). Recent studies showed that several pathways may be upregulated in inbred as compared with outbred Drosophila individuals, whereas others, though less commonly occurring, are downregulated (Kristensen et al, , 2006Pedersen et al, 2005;GarcĂ­a et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to draw on a large pool of genetic variation allows hosts to respond adaptively to such challenges and thus inbreeding places populations at a competitive disadvantage by depriving them of their ability to co-evolve defenses against pathogenic invaders (Stow and Beattie, 2008). Moreover, inbreeding can have negative effects on overall health as genetic drift allows disadvantageous traits to reach fixation (Reid et al, 2003;Calleri et al, 2006;Ilmonen et al, 2008). Consequently, inbred individuals may have poorly adapted or disabled immune pathways or fewer resources available with which to respond to novel parasites and pathogens (Rantala and Roff, 2007).…”
Section: Introductionmentioning
confidence: 99%